2023
DOI: 10.3390/ijms24065124
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of the Complexities of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome and Long COVID

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex condition arising in susceptible people, predominantly following viral infection, but also other stressful events. The susceptibility factors discussed here are both genetic and environmental although not well understood. While the dysfunctional physiology in ME/CFS is becoming clearer, understanding has been hampered by different combinations of symptoms in each affected person. A common core set of mainly neurological symptoms forms the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 122 publications
0
27
0
1
Order By: Relevance
“…Finally, focusing on the manipulation of the microbiome followed by other areas highlighted to be of the most therapeutic value including energy metabolism, chronic inflammation, fluctuating neuroinflammation and management of the response to stress [13] could provide holistic background supporting the most promising probiotic interaction in the care offered for patients suffering from post-viral syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, focusing on the manipulation of the microbiome followed by other areas highlighted to be of the most therapeutic value including energy metabolism, chronic inflammation, fluctuating neuroinflammation and management of the response to stress [13] could provide holistic background supporting the most promising probiotic interaction in the care offered for patients suffering from post-viral syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Reported association between low levels of butyrate, as well as reduced abundance of SCFAs producing bacteria in expense of gut pathogens with persisting GI and neurological symptoms in these individuals, highlighted the need for novel strategies for microbiome-tailored disease prevention and treatment. The increased interest and research activity initiated during COVID-19 pandemic, based on the certain similarity observed in pathophysiology of both post-viral syndromes, in particularly in the gut microbiome, may accelerate the progress in developing evidence-based therapeutic options for ME/CFS [13] such as use of microbial preparations.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es kommen medikamentöse und nicht-medikamentöse Maßnahmen zum Einsatz, z. B. Analgetika, Inhalativa, Kreislaufmedikamente, Antihistaminika, Psycho- sowie Physiotherapie 5 , 7 , 18 . Im Falle von Belastungsintoleranz mit PEM hat sich — basierend auf dem Wissen zu ME/CFS — das Pacing als hilfreiche Strategie bewährt.…”
Section: Hintergrundunclassified
“…Long COVID can affect individuals varying in the severity of initial infection, including asymptomatic children/adolescents [19]. Long-term longitudinal clinical and -omics studies are needed to determine if long COVID can lead to distinct subgroups using cluster analysis in some individuals with ME/CFS and FM [20,21]. ME/CFS, FM, and long COVID can occur independently or an coexist in some individuals with other comorbid health conditions, such as irritable bowel syndrome (IBS), and mood disorders, such as anxiety/depression, which can further complicate the understanding and management of these conditions [22].…”
Section: Introductionmentioning
confidence: 99%